Activation of AKT negatively regulates the pro-apoptotic function of death-associated protein kinase 3 (DAPK3) in prostate cancer. Issue 2 (28th July 2016) - Das, Trinath P.; Suman, Suman; Papu John, A.M. Sashi; Pal, Deeksha; Edwards, Angelena; Alatassi, Houda; Ankem, Murali K.; Damodaran, Chendil
Highlights: This is the first study that demonstrates the inverse correlation of AKT activation and down-regulation of tumor suppressor protein, DAPK-3, in CaP cell lines as well as human prostate tumor tissues that correlate with disease progression. Either silencing AKT or overexpressing DAPK-3 induces apoptosis in Castration Resistant Prostate Cancer cells. Abstract: The activation of AKT governs many signaling pathways and promotes cell growth and inhibits apoptosis in human malignancies including prostate cancer (CaP). Here, we investigated the molecular association between AKT activation and the function of death-associated protein kinase 3 (DAPK3) in CaP. An inverse correlation of pAKT and DAPK3 expression was seen in a panel of CaP cell lines. Inhibition of AKT by wortmannin/LY294002 or overexpression of DAPK3 reverts the proliferative function of AKT in CaP cells. On the other hand, ectopic expression of AKT inhibited DAPK3 function and induced proliferation of CaP cells. In addition, AKT over-expressed tumors exhibit aggressive growth when compared to control vector in xenograft models. The immunohistochemistry results revealed a down-regulation of DAPK3 expression in AKT over-expressed tumors as compared to control tumors. Finally, we examined the expression pattern of AKT and DAPK3 in human CaP specimens – the expected gradual increase and nuclear localization of pAKT was seen in higher Gleason score samples versus benign hyperplasia (BPH). On the contrary, reduced expression of DAPK3 was seen in higher Gleason stages versus BPH. This suggests that inhibition of DAPK3 may be a contributing factor to the carcinogenesis of the prostate. Understanding the mechanism by which AKT negatively regulates DAPK3 function may suggest whether DAPK3 can be a therapeutic target for CaP.